(untitled) (Sociología y tecnociencia, 2023)
Digital skills are increasingly necessary. When their level is unequal, problems of exclusion can arise in the regional and gender spheres. This paper analyzes both types of digital divides in Spain and their recent evolution. The indicator used is IRIS-DESI and its five dimensions: Connectivity, Human capital, Internet use, Integration of digital technology in companies and Digital public services. Using a hierarchical cluster analysis, the Spanish regions are classified according to their digital development. However, considering the gender gap, no clear regional pattern has been found, possibly due to the very complex and multifaceted nature of the digital economy.